The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/1982-0224-20130174
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic study of Hoplias microlepis (Günther, 1864), a trans-Andean species of trahiras (Ostariophysi: Characiformes: Erythrinidae)

Abstract: The Hoplias malabaricus species group represents one of the most complexes taxonomical problems in the systematics of Neotropical fishes, including specimens widely distributed in most drainages of South America and part of Central America with great variation or overlap of putative diagnostic characters. The large number of nominal species, many of which without known type material, renders the problem more complicated. Currently, at least three nominal species can be included in the Hoplias malabaricus speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 864 publications
(14 citation statements)
references
References 26 publications
(28 reference statements)
0
14
0
Order By: Relevance
“…All analyses suggest that Hoplias malabaricus is a species complex containing two well‐structured lineages that, despite being morphologically indistinguishable, co‐occur at the same locations in the Catatumbo and Ranchería rivers without much gene exchange. Hoplias malabaricus is a widespread complex distributed in most drainages of South America (Mattox, Bifi, & Oyakawa, ; Rosso et al, ) that may in fact include many different species throughout its range. Cytogenetic studies have also reported sympatric lineages of H. malabaricus in the Doce River in Brazil and in the Ctalamochita River in Argentina with co‐occurring individuals having different karyotypes (Born & Bertollo, ; Grassi, Swarça, Dergam, Pastori, & Fenocchio, ; Jacobina, Paiva, & Dergam, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All analyses suggest that Hoplias malabaricus is a species complex containing two well‐structured lineages that, despite being morphologically indistinguishable, co‐occur at the same locations in the Catatumbo and Ranchería rivers without much gene exchange. Hoplias malabaricus is a widespread complex distributed in most drainages of South America (Mattox, Bifi, & Oyakawa, ; Rosso et al, ) that may in fact include many different species throughout its range. Cytogenetic studies have also reported sympatric lineages of H. malabaricus in the Doce River in Brazil and in the Ctalamochita River in Argentina with co‐occurring individuals having different karyotypes (Born & Bertollo, ; Grassi, Swarça, Dergam, Pastori, & Fenocchio, ; Jacobina, Paiva, & Dergam, ).…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic studies have also reported sympatric lineages of H. malabaricus in the Doce River in Brazil and in the Ctalamochita River in Argentina with co‐occurring individuals having different karyotypes (Born & Bertollo, ; Grassi, Swarça, Dergam, Pastori, & Fenocchio, ; Jacobina, Paiva, & Dergam, ). Hoplias microlepis (formerly H. malabaricus ) has been recently described from the Pacific drainages of Panamá and Southwestern Costa Rica based on examination of syntypes and other specimens (Mattox et al, ). Ultimately, our results highlight the need of a comprehensive phylogeographic analysis of the H. malabaricus species complex based on material collected throughout its distributional range as well as an in‐depth taxonomic revision, including the description of many potential new species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, cryptic diversity doubling the original number of valid species was detected within the genus Curimatopsis (Melo, Ochoa, Vari, & Oliveira, ). The Hoplias malabaricus species complex has been receiving particular attention during recent years (Mattox, Bifi, & Oyakawa, ) and two new species (Azpelicueta, Benítez, Aichino, & Mendez, ; Rosso et al, ) have been formally described recently. Cryptic diversity in the freshwater pufferfish genus Colomesus (Amaral, Brito, Silva, & Carvalho, ), and in pencilfishes of the genus Nannostomus (Benzaquem, Oliveira, da Silva Batista, Zuanon, & Porto, ) have also been revealed.…”
Section: Discussionmentioning
confidence: 99%